Institutional Analysis of Human Resources Allocation for University Teachers - A Case Study of Tsinghua University - Wang, Zihao (Transactions on Economics, Business and Management Research, 2024)
In recent years, many colleges and universities in China have encountered various problems in the management of teachers’ human resources, such as unreasonable internal teacher distribution structure and regional imbalance of educational resources, loose performance appraisal system and unrigorous supervision, lack of incentive mechanism, research and exploration motivation of teachers and students, serious recessive loss of human resources and so on. Human resource management is an indispensable part of every school, which plays an important role in learning efficiency and teaching quality. At present, this study explores the above four small problems and corresponding suggestions and improvement measures. But much remains unknown about the deeper research and the underlying problems hidden inside. The theme of the study is a multi-faceted exploration of the education field with human resource management as the core, and it is comprehensively collated through the literature produced in the field of human resources in recent years by many institutions of higher learning, led by Tsinghua University. The research finds that the reasons for the problems and contradictions in classroom human resource management in most colleges and universities are similar, and the main reasons are bad treatment, heavy workload, lack of care. Therefore, suggestions are put forward for regional coordination and common development, strengthening assessment and supervision system, improving incentive mechanism, strengthening talent reserve.